Literature Review: The Effectiveness of Group Guidance Services to Increase Student Self-Confidence - Yuliska Putri, Fharoza; Nurwahidin, Muhammad; Rahmayanthi, Ranny; Yulianti, Dwi (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2024)
This study aims to explore the effectiveness of group guidance services in increasing students’ self-confidence. The research method used is a literature study to gather empirical evidence from various sources relevant to this topic. The results of the analysis show that group guidance services can be effective in increasing students’ self-confidence through several mechanisms, including social skill building, emotional peer support, identification of self-potential, and development of problem-solving strategies. Nonetheless, variations in program design, mentor qualifications, and individual student characteristics may affect the success rate of these programs. Thus, this study highlights the importance of further research to better understand the factors that influence the effectiveness of group guidance in the context of improving students’ self-confidence.